2017
DOI: 10.1159/000485819
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen-G Inhibits the Anti-Tumor Effect of Natural Killer Cells via Immunoglobulin-Like Transcript 2 in Gastric Cancer

Abstract: Background/Aims: Human leukocyte antigen-G (HLA-G) plays an important role in inhibiting natural killer (NK) cell function and promoting immune escape. However, the specific mechanism of HLA-G on NK in gastric cancer (GC) remains not well understood. This study investigated the expression of HLA-G in GC and the role of HLA-G-effected NK cells in GC progression. Methods: HLA-G expression in GC tissues obtained from 49 patients with GC was analyzed by immunohistochemistry and western blot. The number of tumor-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 67 publications
0
35
0
1
Order By: Relevance
“…HLA-G1/ILT2 interaction was also shown to mitigate MICA/NKG2D activation by inhibiting NK cytotoxicity (117). In gastric cancers, HLA-G/ILT2 interaction led to inhibition of infiltrating NK cell proliferation and cytotoxicity (118). HLA-G plasma expression in B-cell malignancies, however, has been shown to inhibit malignant B cell proliferation due to their expression of ILT2 surface receptors, which is lacking in solid tumor cells (102,119).…”
Section: Lirs (Ilts)mentioning
confidence: 99%
“…HLA-G1/ILT2 interaction was also shown to mitigate MICA/NKG2D activation by inhibiting NK cytotoxicity (117). In gastric cancers, HLA-G/ILT2 interaction led to inhibition of infiltrating NK cell proliferation and cytotoxicity (118). HLA-G plasma expression in B-cell malignancies, however, has been shown to inhibit malignant B cell proliferation due to their expression of ILT2 surface receptors, which is lacking in solid tumor cells (102,119).…”
Section: Lirs (Ilts)mentioning
confidence: 99%
“…Its expression and functionality in the tumor microenvironment have drawn great attention since last decade. We found that enriched ILT4 expression is the common feature for malignancies including NSCLC, breast cancer, hepatocellular carcinoma and colorectal cancer [11,[24][25][26]. The subsequent investigation from our and other groups demonstrated that tumor cell-derived ILT4 supported tumor growth and metastasis through induction of their malignant behaviors such as proliferation, invasion, migration, EMT and HSC self-renewal [12][13][14]27].…”
Section: Discussionmentioning
confidence: 63%
“…In gastric cancer cells, TGF-β induces HLA-G expression through miR-152 inhibition, which results in the suppression of NK cell functions mediated by the interaction between HLA-G and the receptor ILT2 [58,59]. In agreement with this evidence, HLA-G induction is guided by TGF-β in ovarian cancer and in pancreatic adenocarcinoma cells where the cytokine increases also the surface levels of HLA-E, the ligand for the NK cell inhibitory receptor NKG2A [60,61].…”
Section: Regulation Of Nk Cell Inhibitory Signals By Tgf-βmentioning
confidence: 99%